Does the clinical phenotype of mucolipidosis-III gamma differ from its alpha beta counterpart?: supporting facts in a cohort of 18 patients - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2019)
Mucolipidosis-III gamma (ML-III gamma) is a recessively inherited slowly progressive skeletal dysplasia caused by mutations in GNPTG. We report the genetic and clinical findings in the largest cohort with ML-III gamma so far: 18 affected individuals from 12 families including 12 patients from India, five from Turkey, and one from the USA. With consanguinity confirmed in eight of 12 families, molecular characterization showed that all affected patients had homozygous pathogenic GNPTG genotypes, underscoring the rarity of the disorder. Unlike ML-III alpha beta, which present with a broader spectrum of severity, the ML-III gamma phenotype is milder, with onset in early school age, but nonetheless thus far considered phenotypically not differentiable from ML-III alpha beta. Evaluation of this cohort has yielded phenotypic findings including hypertrophy of the forearms and restricted supination as clues for ML-III gamma, facilitating an earlier correct choice of genotype screening. Early identification of this disorder may help in offering a timely intervention for the relief of carpal tunnel syndrome, monitoring and surgery for cardiac valve involvement, and evaluation of the need for joint replacement. As this condition may be confused with rheumatoid arthritis, confirmation of diagnosis will prevent inappropriate use of immunosuppressants and disease-modifying agents. Copyright (c) 2018 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: carpal tunnel syndrome; clawing of fingers; genu valgum; GNPTG; hypertrophy of forearm; mucolipidosis-III alpha beta; mucolipidosis III gamma; PSEUDO-HURLER POLYDYSTROPHY; I-CELL DISEASE; LYSOSOMAL-ENZYMES; MUTATIONS; GNPTAB; IDENTIFICATION; GENOTYPE; MANNOSE; SUBUNIT